Gastric ulcer in the distant evolution of the duodenal ulcer treated by gastroenterostomy - Suiffet, Walter; Castiglioni, J C (Cirugía del Uruguay, 1972)
Two patients with duodenal ulcers and piloric obtructive syndrome had unrler gone gastroenterostomy far from the pilorus ( 28 and 32 years earlier). They later developed stomach ulcers complicated by haemorrhages. They were cured through degastroenterostomy and subtotal gastrectomy 75 % Billroth II. The different pathogenical hypothesis of gastric ulcers are discussed. Hyperacydity of antral gastrinic origin is considered the genetical ele.ment of gastric ulcers; this thesis is supported by the two clinical cases mentioned.